370. Efficacy of Cochleated Amphotericin B (C-AMB) in Mouse Models of Oropharyngeal and Vulvovaginal Candidiasis. (26th November 2018) - Desai, Jigar V; Lu, Ruying; Freeman, Alexandra F; Tramont, Edmund; Jabbour, Jerry; Mannino, Raphael J; Lionakis, Michail S
Abstract: Background: Candida albicans causes debilitating mucosal infections in patients with inherited susceptibility to chronic mucocutaneous candidiasis (CMC) such as oropharyngeal candidiasis (OPC) and vulvovaginal candidiasis (VVC), which often require long-term azole-based treatment. Due to the high incidence of azole resistance in these patients, alternative treatment options are desirable. Acquired resistance against amphotericin B (AMB) has not been documented but parenteral administration of AMB is associated with nephrotoxicity and infusion reactions. Cochleated AMB (C-AMB) is a new formulation of AMB designed for oral administration and thus an attractive treatment option for OPC and VVC. The purpose of our study was to assess the efficacy of C-AMB in mouse models OPC and VVC. Methods: IL-17 signaling deficient mice ( Act1 −/− ) were infected with a clinical isolate of C. albicans in models of OPC and VVC. From day 1 post-infection (pi) through day 4 pi, mice were treated once daily via oral gavage with C-AMB or placebo or intraperitoneal AMB-deoxycholate (AMB-d). At day 5 pi, the mice were euthanized and tongue tissue (OPC) or vaginal fluid and vaginal tissue (VVC) were harvested to quantify fungal burden. Results: During OPC, mice treated with C-AMB (25 or 83.5 mg/kg/day) displayed significantly reduced tongue fungal burden compared with placebo-treated mice and comparable to that observed in mice treated with intraperitoneal AMB-d (25 mg/kg/day). During VVC, mice treated with C-AMB exhibited significantly decreased fungal burden in vaginal tissue, but not vaginal fluid, relative to placebo-treated mice. Conclusion: Oral administration of C-AMB in IL-17-signaling deficient mice results in a reduction in tongue and vaginal tissue fungal burden during mucosal C. albicans infections. Ongoing studies are aimed at characterizing the distribution of C-AMB in mouse mucosal tissues and examining C-AMB efficacy relative to fluconazole. Disclosures: R. Lu, Matinas BioPharma Inc.: Employee, Salary. A. F. Freeman, Matinas BioPharma Inc.: Research Support, Research support. J. Jabbour, Matinas BioPharma Inc.: Employee, Salary. R. J. Mannino, Matinas BioPharma Inc.: Employee, Salary. M. S. Lionakis, Matinas BioPharma Inc.: Research support, Research support.